(3x2 - 6x + 7).(4ax2) =
3x2.4ax2 - 6x-4ax2 + 7.4ax2 =
3. 4ax2+2 - 6 - 4ax2+1 +7 · 4ax2
12ax4 - 24ax3 + 28ax?
Respuestas a la pregunta
Contestado por
2
Respuesta:
hola
Explicación:
3x2 - 6x + 7).(4ax2) = 5x 5
3x2.4ax2 - 6x-4ax2 + 7.4ax2 =533
3. 4ax2+2 - 6 - 4ax2+1 +7 · 4ax2
12ax4 - 24ax3 + 28ax?
torresabigail671:
gracias....
Otras preguntas
Matemáticas,
hace 3 meses
Matemáticas,
hace 3 meses
Ciencias Sociales,
hace 6 meses
Exámenes Nacionales,
hace 6 meses
Biología,
hace 11 meses
Castellano,
hace 11 meses